Association of carbohydrate and fat intake with metabolic syndrome. Issue 2 (April 2018) - Kwon, Yu-Jin; Lee, Hye-Sun; Lee, Ji-Won
Summary: Background & aims: In Asia, dietary pattern has been changed with increased intake of refined carbohydrates, sugar, and saturated fat, while the prevalence of metabolic syndrome (MetS) is on the rise. However, it remains unclear whether a high-carbohydrate or a high-fat diet is more metabolically harmful, and the optimal amount of carbohydrates and fat has not been determined. The aim of our study was to examine the role of carbohydrate and fat intake in MetS in a Korean population. Methods: Data were obtained from a large, population-based, cross-sectional study (6737 males and 8845 females). The subjects were divided into nine groups based on carbohydrate and fat proportion, and multiple logistic regression analysis was performed after adjusting for confounding variables. Results: Regardless of fat intake, the risk of MetS significantly increased in males with higher carbohydrate proportions (of total energy intake). In females, the risk of MetS was significantly elevated only in those with both the highest carbohydrate proportion and lowest fat proportion. Conclusion: A high carbohydrate proportion was associated with a higher prevalence of MetS in males, and a high carbohydrate proportion combined with a low fat proportion was associated with MetS in females. Our results indicate that reduction of excessive carbohydrate intake paired with an adequate fat intake, taking into consideration optimal types of fat, is useful for MetS prevention. Longitudinal studies are needed to clarify the optimal types and amounts of carbohydrate and fat proportions as well as the mechanism underlying these relationships. Highlights: We examined the role of carbohydrate and fat in metabolic syndrome. This study was cross-sectionally designed based on the 2008–2011 KNHANES. Participants were categorized to nine groups based on carbohydrate and fat proportion. A higher carbohydrate proportion is associated with a higher prevalence of MetS in men. A high carbohydrate proportion with a low fat proportion is associated with MetS in women.